2014
DOI: 10.4322/polimeros.2014.048
|View full text |Cite
|
Sign up to set email alerts
|

Metal Nanoparticles/Ionic Liquid/Cellulose: Polymeric Membrane for Hydrogenation Reactions

Abstract: Rhodium and platinum nanoparticles were supported in polymeric membranes with 10, 20 and 40 μm thickness. The polymeric membranes were prepared combining cellulose acetate and the ionic liquid (IL) 1-n-butyl-3-methylimidazolium bis(trifluoromethane sulfonyl)imide (BMI.(NTf) 2 . The presence of metal nanoparticles induced an increase in the polymeric membrane surface areas. The increase of the IL content resulted in an improvement of elasticity and decrease in tenacity and toughness, whereas the stress at break… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
0
1
0
1
Order By: Relevance
“…The metal concentration incorporated in the polymeric membrane is related to the thickness of the membrane; it was observed that, for thickness up to 20 mm, the materials is saturated by 10 mg of nanoparticles. 46 The presence of the IL in the polymeric membranes was conrmed by the stretching band at 3170 cm À1 , which is due to presence of aromatic C-H groups. Aer impregnation of the IL in the polymeric membranes, a signicant decrease is observed in the intensity of the band at 3400 cm À1 , which is attributed to the -OH stretching of the pure cellulose acetate, indicating participation of the -OH group in the interaction with the IL (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The metal concentration incorporated in the polymeric membrane is related to the thickness of the membrane; it was observed that, for thickness up to 20 mm, the materials is saturated by 10 mg of nanoparticles. 46 The presence of the IL in the polymeric membranes was conrmed by the stretching band at 3170 cm À1 , which is due to presence of aromatic C-H groups. Aer impregnation of the IL in the polymeric membranes, a signicant decrease is observed in the intensity of the band at 3400 cm À1 , which is attributed to the -OH stretching of the pure cellulose acetate, indicating participation of the -OH group in the interaction with the IL (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…18,19 Recentemente também foi demonstrado que a combinação de NPs metálicas estáveis em líquidos iônicos (LIs) com um filme polimérico de celulose pode gerar um material novo e versátil. 20 Nestas práticas experimentais, nós demonstramos a combinação de NPs de Au sintetizadas em líquido iônico BMI. PF 6 suportadas em filme biopolimérico de acetato de celulose com investigação em atividade antimicrobiana frente as bactérias S. aureus e E. coli.…”
Section: Introductionunclassified